Inulin with a low degree of polymerization protects human umbilical vein endothelial cells from hypoxia/reoxygenation-induced injury. (15th July 2019) - Cha, Xuexiang; Han, Shengna; Yu, Jian; Zhang, Saiyang; Yu, Shuang; Fu, Dongjun; Yao, Min; Zhang, Lirong; Feng, Guoqing
Graphical abstract: Highlights: We identified inulins with 3–13 degrees of polymerization from Morinda officinalis. Inulins 4–7 had modest anti-oxidative effects, and inulin 5 promoted angiogenesis. Inulins 4 and 5 increased HUVEC survival during H/R-induced injury. Inulins were found to activate the PI3K–PKB–eNOS-signaling pathway. Inulins from M. officinalis roots may protect against H/R-induced tissue injury. Abstract: Here, we identified inulin-type oligosaccharides with 3–13 degrees of polymerization from Morinda officinalis . Radical-scavenging assays showed that Inulins 4–7 had modest anti-oxidative effects. Inulins 4 and 5 dose-dependently increased human umbilical vein endothelial cell survival during hypoxia/re-oxygenation (H/R)-induced injury, and Inulin 5 promoted angiogenesis. Triplicate assays with the Affymetrix Human Transcriptome Array 2.0 showed that Inulin 5 exposure up-regulated genes associated with cell cycle progression, apoptosis, DNA replication and repair, ubiquitin-mediated proteolysis, the mitogen-activated protein kinase pathway, and the phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K)-signaling pathway. Flow cytometry, reverse transcription-quantitative polymerase chain reaction, and western blot experiments verified the microarray results and demonstrated that Inulin 5 influenced cell cycle progression and the PI3K–protein kinase B (PKB)–endothelial nitric oxide synthase (eNOS) pathway. Thus, inulin-type oligosaccharides from M. officinalis roots may protect against H/R-induced injury, primarily through an anti-oxidative effect, and promote angiogenesis by activating the PI3K–PKB–eNOS-signaling pathway.